Gearing system of a weaving loom / Nur Farah Azrina Thajmy … [et al.] - Thajmy, Nur Farah Azrina; Hazmi, Hazwani Fairuz; Che Roni, Nur Azlin Syahida; Marsat, Normah; Mohd Zaini, Nur Adibah; Musa, Atiyyah; Mohd Razali, MohdTaufiqil Hafiz (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
In weaving technology, loom or weaving machine is invented to aid the process of manufacturing woven fabric. There are 3 primary motions involved in loom; namely shedding, picking and beating. These motions are governed by gearing system. It was a great challenge to understand the loom gearing system without a tool to simulate the function. Furthermore, in a real loom this part is normally covered for safety purposes. Thus, this portable scale down sized loom is created as one of the teaching and learning tool in class to assist in understanding of the gearing system. The system comprises of three shafts; crank, bottom and tappet, where every shaft is responsible for the primary motions stated earlier. Via this invention, it is hoped that students now could have better opportunity and space to explore what the loom has offered.